Statistical analysis of disability in spinal injury and spinal cord injury - Pedachenko, E. G.; Ipatov, A. V.; Tarasenko, O. M. (Zaporozhye Medical Journal, 2013)
Spinal trauma is one of the most challenging problems of modern neurosurgery. In the USA every year about 8-10 thousand new cases of the complicated spinal trauma are recorded, in Ukraine this number is 2-3 thousand in a year. The results of examination of 130 patients with spinal trauma by medical and social examination departments were analized. All patients were acknowledged as invalids, or their sick-leaves were prolonged for further treatment and subsequent re-examination. The analysis of disability was conducted depending on a sex, hardness and level of trauma and further employment of patients was observed.